Evaluation of vaginal mRNA markers in women from different age groups: A GeFI collaborative study. Issue 1 (December 2019) - Robino, C.; Chierto, E.; Alessandrini, F.; Bini, C.; Carnevali, E.; Fabbri, M.; Fattorini, P.; Grignani, P.; Scarnicci, F.; Tozzo, P.; Verzeletti, A.; Pelotti, S.; et al.
Abstract: Forensic mRNA profiling assays normally include a set of vaginal-specific markers. Although it is known that vagina undergoes characteristic age-related morphological and physiological changes over a lifetime, few studies have evaluated the efficacy of proposed forensic vaginal mRNA markers in women from different age groups. In this collaborative study involving ten GeFI (Italian working group of ISFG) laboratories, a 19-plex mRNA profiling assay including three vaginal-specific markers (CYP2B7P1, MUC4, MYOZ1) was tested in a collection of vaginal swabs obtained from female volunteer donors in their reproductive years (n = 84) and postmenopausa (n = 55). Differential expression of vaginal markers in the two age categories was assessed by means of: a) overall success rate of mRNA profiling (vaginal mucosa "observed" in the tested sample according to scoring protocol) b) average peak height ratios between vaginal-specific markers within mRNA profiling replicates. Other factors potentially influencing mRNA profiling outcomes, like time interval between vaginal swab collection and analysis, concurrence of menstrual cycle and recent sexual activity at the time of sampling were also investigated.